DOP60 Environmental risk factors for Inflammatory bowel disease: A large prospective case-control study in India. (30th January 2023) - Banerjee, R; Pal, P; Prakash, N; Mudigonda, S; Joseph, S; Patel, R; Khalil, M; Komawar, A; Korikana, S; Mekala, D; Akki, Y; Gaddam, A; et al.
Abstract: Background: Increasing urbanization and westernization of lifestyles have been implicated for the rising incidence of IBD in the developing world. However real world data is very limited. We planned a comprehensive assessment of environmental exposures in a large cohort of patients with and without IBD in India to identify key risk factors. Methods: This study is a part of a wider epidemiologic colonoscopic screening program for detection of IBD on all symptomatic patients attending the hospital and specially conducted rural health camps. A detailed questionnaire based survey of environmental risk factors including diet, smoking, antibiotic use, hygiene status, microbial exposures, vaccination, water supply, rural/urban residence was conducted prior to colonoscopy. The risk factors were compared among the IBD and non IBD patients with normal colonoscopy. Univariate logistic regression was done initially adjusting for age and sex followed by multivariate analysis to estimate adjusted ORs (aOR) and 95% CIs. Results: 13421 completed environmental risk questionnaire.1306 IBD(576 CD;730 UC) cases diagnosed.12115 with normal colonoscopy served as the controls. In multivariate model, current smoking(aOR 5.66; 95% CI 4.41-7.26), ex-smoking (aOR 1.79;1.24-2.58), regular alcohol intake (aOR 1.82, 1.14-2.9), non-vegetarian diet(aOR 1.8; 1.48-2.23), daily bakery/fast food consumption(aOR 1.57; 1.31-1.88), soft drink consumption(> 2/week)(aOR 1.37, 1.14-1.66), delivery by cesarean section (aOR 1.49, 95% CI 1.28-1.76), antibiotic use(<1 yr age) (aOR1.33;1.1-1.58), exposure to pets(aOR 1.68;1.39-2.03), Western toilets (aOR3.52, 2.56-3.58)and childhood infections (aOR 1.74; 1.45-2.028) increased risk of UC (Fig 1, 2). Increased risk of CD was seen with current smoking(aOR 6.16; 95% CI 4.68-8.11), ex-smoking(aOR2.15; 1.43-3.22), non-vegetarian diet (aOR 1.69;1.34-2.13), soft drink consumption(> 2/week)(aOR 1.84, 1.51-2.24), daily bakery/fast food consumption(aOR 2.24;1.85-2.71), oral contraceptive pill use (aOR 3.79, 1.29-12.17) antibiotic use (<1 year age)(aOR 1.27; 1.04-1.54), exposure to pets(aOR 1.79; 1.45-2.2), caesarean section(aOR 1.48;1.23-1.77), Western toilets (aOR 2.98, 2.47-3.59), non-human milk exposure (<6 months age) (aOR 1.28, 1.03-1.6) and childhood infections(aOR 2.51; 2.1-3.04)(Fig 3, 4). Breastfeeding >6 months, daily fruit consumption and daily exercise were protective for both UC and CD (Fig1-4).Rural habitat was not protective for development of IBD both UC and CD. Conclusion: This large prospective case control study of IBD risk factors in India identifies environmental triggers including childhood immunological, hygiene and dietary factors which modulate risk of IBD later in life.